Methylobacterium populi VP2: Plant Growth-Promoting Bacterium Isolated from a Highly Polluted Environment for Polycyclic Aromatic Hydrocarbon (PAH) Biodegradation - Valeria Ventorino; Filomena Sannino; Alessandro Piccolo; Valeria Cafaro; Rita Carotenuto; Olimpia Pepe (The Scientific World Journal)
The use of microorganisms to accelerate the natural detoxification processes of toxic substances in the soil represents an alternative ecofriendly and low-cost method of environmental remediation compared to harmful incineration and chemical treatments. Fourteen strains able to grow on minimal selective medium with a complex mixture of different classes of xenobiotic compounds as the sole carbon source were isolated from the soil of the ex-industrial site ACNA (Aziende Chimiche Nazionali Associate) in Cengio (Savona, Italy). The best putative degrading isolate, Methylobacterium populi VP2, was identified using a polyphasic approach on the basis of its phenotypic, biochemical, and molecular characterisation. Moreover, this strain also showed multiple plant growth promotion activities: it was able to produce indole-3-acetic acid (IAA) and siderophores, solubilise phosphate, and produce a biofilm in the presence of phenanthrene and alleviate phenanthrene stress in tomato seeds. This is the first report on the simultaneous occurrence of the PAH-degrading ability by Methylobacterium populi and its multiple plant growth-promoting activities. Therefore, the selected indigenous strain, which is naturally present in highly contaminated soils, is good candidate for plant growth promotion and is capable of biodegrading xenobiotic organic compounds to remediate contaminated soil alone and/or soil associated with plants.